We've got a job : the 1963 Birmingham Children's March - Levinson, Cynthia (New York : Scholastic, 2012)
Discusses the events of the 4,000 African American students who marched to jail to secure their freedom in May 1963.
Includes bibliographical references (p. 170-171) and index.
Keywords: African Americans -- Civil rights -- Alabama -- Birmingham -- History -- 20th century -- Juvenile literature; Civil rights movements -- Alabama -- Birmingham -- History -- 20th century -- Juvenile literature; African American students -- Alabama -- Birmingham -- History -- 20th century -- Juvenile literature; African American youth -- Alabama -- Birmingham -- History -- 20th century -- Juvenile literature